Neighbourhood-based participatory action research with older adults: Facilitating participation through virtual and remote methods - Carri Hand; Andrea Keber; Jami McFarland; Colleen McGrath; Debbie Laliberte Rudman; Lewis Seale; Jason Gilliland; Shirley Little (Methodological Innovations)
Participatory action research (PAR) is an effective means of collaborating with older adults to support community change. Limited PAR literature exists in which older adults catalyse social change within neighbourhoods, particularly using virtual methods. In this paper, we discuss a virtual PAR process with older adults that occurred during the COVID-19 pandemic, and the results of inquiry into our application of PAR principles. We conducted PAR in a collective involving university researchers, older adult residents and community partners in an urban core neighbourhood in a mid-sized Canadian city and focused on enhancing daily life for older adults. The PAR project emerged through reflection on previous ethnographic findings regarding older adults’ daily life in neighbourhoods. Our PAR collective collaboratively identified a need among older adults for more accessible information about community resources. To support older adults’ participation and access to community information, the PAR collective created and distributed a free neighbourhood resource booklet, in print and digital formats, to promote equitable access. We evaluated the impact of the booklet through a survey and discussions with community partners. During our PAR process we found challenges and solutions related to using technology, engaging in discussion during virtual meetings, and making collaborative decisions. A combination of in-person, remote and online interactions seemed to facilitate relationship development amongst co-researchers and completion of the project. Future PAR projects would benefit from incorporating in-person, remote and online methods from the outset, as well as ways to support older adults in using and accessing technology. We further noted the value of a local resource booklet, in print and digital formats, in promoting neighbourhood information sharing.